A mitochondrial long-chain fatty acid oxidation defect leads to transfer RNA uncharging and activation of the integrated stress response in the mouse heart. Issue 16 (7th April 2022) - Ranea-Robles, Pablo; Pavlova, Natalya N; Bender, Aaron; Pereyra, Andrea S; Ellis, Jessica M; Stauffer, Brandon; Yu, Chunli; Thompson, Craig B; Argmann, Carmen; Puchowicz, Michelle; Houten, Sander M
Abstract: Aims: Cardiomyopathy and arrhythmias can be severe presentations in patients with inherited defects of mitochondrial long-chain fatty acid β-oxidation (FAO). The pathophysiological mechanisms that underlie these cardiac abnormalities remain largely unknown. We investigated the molecular adaptations to a FAO deficiency in the heart using the long-chain acyl-CoA dehydrogenase (LCAD) knockout (KO) mouse model. Methods and results: We observed enrichment of amino acid metabolic pathways and of ATF4 target genes among the upregulated genes in the LCAD KO heart transcriptome. We also found a prominent activation of the eIF2α/ATF4 axis at the protein level that was independent of the feeding status, in addition to a reduction of cardiac protein synthesis during a short period of food withdrawal. These findings are consistent with an activation of the integrated stress response (ISR) in the LCAD KO mouse heart. Notably, charging of several transfer RNAs (tRNAs), such as tRNA Gln was decreased in LCAD KO hearts, reflecting a reduced availability of cardiac amino acids, in particular, glutamine. We replicated the activation of the ISR in the hearts of mice with muscle-specific deletion of carnitine palmitoyltransferase 2. Conclusions: Our results show that perturbations in amino acid metabolism caused by long-chain FAO deficiency impact cardiac metabolic signalling, in particular the ISR. These results may serve as a foundation for investigating the role of the ISR in the cardiac pathology associated with long-chain FAO defects. Translational Perspective: The heart relies mainly on mitochondrial fatty acid β-oxidation (FAO) for its high energy requirements. The heart disease observed in patients with a genetic defect in this pathway highlights the importance of FAO for cardiac health. We show that the consequences of a FAO defect extend beyond cardiac energy homeostasis and include amino acid metabolism and associated signalling pathways such as the integrated stress response. Graphical Abstract: Graphical Abstract